Potential mechanisms and effects of AFB1-induced asthma: A comprehensive analysis based on network toxicology and molecular docking - Zhiyue Yu; Ming Gao; Xiaowen Wu; Jiaxiang Li; Baijun Liu; Rui Wang; Jing Tan; Xiangyan Yu; Limei Geng (PLoS ONE, 2026)
The aim of this study was to systematically explore the potential molecular mechanisms by which aflatoxin B1 (AFB 1 ) may trigger asthma using network toxicology and molecular docking. Potential targets related to asthma caused by AFB 1 were obtained from databases, such as PubChem, ProTox, ADMETab, and GeneCards. The targets most significantly related to asthma were further screened using STRING and Cytoscape and analyzed using GO and KEGG enrichment. Finally, molecular docking and visualization were performed using AutodockVina 1.2.2 and PyMOL 2.5 to further determine the affinity between AFB 1 and the core targets. We identified 31 potential targets associated with AFB 1 exposure and asthma, including PTGS2, ADRB2, CysLTR1, PTGS1, and others. The enrichment analysis revealed that the core targets of AFB 1 -induced asthma were neuroactive ligand‒receptor interactions, the calcium signaling pathway, and the adipocyte catabolism-related signaling pathway. Molecular docking results revealed that AFB 1 exhibited good affinity for the core targets. In the present study, the potential mechanisms involved in AFB 1 -induced asthma were elucidated, new insights into how environmental toxins trigger asthma were provided, and a theoretical foundation for asthma prevention and treatment was established.